Polymorphism of Qualitative Traits of Arabic Chicken: A Case Study in Polymorphism of Qualitative Traits of Arabic Chicken: A Case Study in Istiqomah Farmer Group, Dasan Cermen, Mataram, West Nusa Tenggara, Indonesia - Tamzil , Mohammad Hasil; Haryani, Ni Ketut Dewi; Jaya, I. Nyoman Sukatha (International Journal of Poultry Science, 2018)
Background and Objective: Data on the polymorphism of qualitative traits of Arabic chicken are not available. The study was designed to determine the variety of qualitative traits of Arabic chickens reared in Mataram city. Methodology: The study was conducted in Istiqomah Farmer Group in Dasan Cermen, Sandubaya, Mataram, Indonesia, using a survey method, in which farmer samples were selected by random sampling purposive method. Collected data were tabulated and analyzed descriptively. Results: The study found that Arabic chickens reared in the city of Mataram had the addition of plumage color, skin color, shank color, beak color and comb shape. The highest frequency of plumage color was silver, followed by golden, gold silver and white gold, respectively. The highest frequency of color of skin, shank and beak was black, followed by white and yellow. The highest frequency of comb shape was singular shape followed by the pea shape. Conclusion: Arabic chickens in Mataram city have been experiencing degradation of colors of plumage, skin, shank, beak and comb shapes.